2017
DOI: 10.1002/hep.29338
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abstinence in patients surviving an episode of alcoholic hepatitis: Prediction and impact on long‐term survival

Abstract: Complete abstinence after an episode of AH positively impacts long-term survival. The combination of 2 variables easily obtained at admission might be useful to predict long-term abstinence after an episode of AH. Strategies aimed at promoting alcohol abstinence in these patients are necessary. (Hepatology 2017;66:1842-1853).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 43 publications
9
109
2
Order By: Relevance
“…On the one hand, the conclusions of this study, and a similar recent prospective account of survivors of severe AH by Louvet et al might, appear prosaic . It is standard practice to urge patients who survive an episode of severe AH to abstain from alcohol.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…On the one hand, the conclusions of this study, and a similar recent prospective account of survivors of severe AH by Louvet et al might, appear prosaic . It is standard practice to urge patients who survive an episode of severe AH to abstain from alcohol.…”
supporting
confidence: 67%
“…For medical caregivers, the events that follow the discharge of those patients who survive are often obscure and given little attention until the next admission. In this issue of Hepatology , Altamirano and colleagues provide a fascinating account of the sequel to an admission in 162 patients with well‐characterized AH, 142 of whom survived to be discharged . Their study is retrospective, but the process of data collection and focus on drinking history mean that it yields several valuable insights.…”
mentioning
confidence: 99%
“…Two studies have already identified alcohol consumption as the main driver of long‐term prognosis in AH patients. In these studies, the other factor associated with outcome was the Lille score in one study, and the MELD score in the other . The present study has the advantage over these 2 studies of using the gs‐MELD score, which has shown better predictive value than either the Lille score or the MELD score alone for short‐term prognosis assessment, as highlighted in the last American Association for the Study of the Liver guidelines .…”
Section: Discussionmentioning
confidence: 66%
“…As alcoholic liver disease has a deep impact on public health and on the liver transplantation waiting list, accurate prediction of both short‐ and long‐term prognosis of patients with severe AH is mandatory for guiding therapeutic strategy . However, only a few studies have evaluated the long‐term prognosis of patients with severe AH . The aim of the present study was to assess the long‐term prognostic value of the gs‐MELD score among patients with severe AH.…”
Section: Introductionmentioning
confidence: 99%
“…AR was defined as the intake of any alcoholic drink after LT. This variable was further categorized as follows: No AR. Heavy AR, which was defined as binge drinking (the consumption of 5 or more SDUs [male] or 4 or more SDUs [female] on a single occasion) or more than 4 drinking days per week Nonheavy AR, which was defined as patients who drink after LT (including slips) and did not fulfill the definition of heavy AR. …”
Section: Methodsmentioning
confidence: 99%